Effect of fermented sausages with probiotic Enterococcus faecium CRL 183 on gut microbiota using dynamic colonic model - Roselino, Mariana Nougalli [UNESP]; Sakamoto, Isabel Kimiko; Tallarico Adorno, Maria Angela; Márcia Canaan, Josiane Maria [UNESP]; de Valdez, Graciela Font; Rossi, Elizeu Antonio [UNESP]; Sivieri, Katia; Umbelino Cavallini, Daniela Cardoso [UNESP] (Elsevier, 2020)
Considering the importance of nutrition in maintaining health conditions, this study is aimed at evaluating the effect of the consumption of a potentially probiotic sausage, with reduction of curing salts and fat, fermented with Enterococcus faecium CRL 183 into the gut microbiota, using the simulator of the human microbial ecosystem (SHIME®). The SHIME® experiment was performed using the probiotic sausage for two weeks. The gut microbiota composition was monitored weekly in all colon vessels by plate counts and denaturing gradient gel electrophoresis (PCR-DGGE). Samples of the colonic contents were evaluated microbiologically by plate counts and denaturing gradient gel electrophoresis (PCR-DGGE) and chemically by the production of SCFA (acetate, propionate and butyrate) and ammonium ions (NH+4). It was observed that the consumption of the potentially probiotic sausage can result in a reduced count of Lactobacillus spp. (colon vessels 3, 4 and 5), Bacteroides spp. (colon vessel 5) and Enterobacteriaceae (colon vessels 4 and 5) and increased levels of ammonium ions. The butyric and propionic acids increased (P < 0.05) while acetic acid decreased (P < 0.05) in treatment period. The PCR-DGGE analysis suggested that probiotic sausage increased the microbiota diversity during the treatment phase. Overall, the findings showed that potentially probiotic sausage represents a healthier alternative of fermented meat, with a positive effect on the microbial diversity and metabolite production.
Keywords: DGGE; Enterococcus faecium CRL 183; Fermented sausage; SCFAs; SHIME